CHARACTERIZATION AND EVALUATION OF SELECTED SOILS OF SOUTHERN NIGERIA FOR RUBBER (Hevea brasiliensis, Muell. Arg.) CULTIVATION (2011)
Successful land management for tree crop production requires good knowledge of the soil variation and suitability for specific tree crops. Most of the traditional rubber growing areas in Nigeria have not been evaluated for their suitability and production potential. Characterisation and evaluation of the land for rubber production was therefore conducted. Soils of two rubber producing areas: Iyanomo, Edo State and Akwete, Abia State were characterised and evaluated using local, United States Department of Agriculture (USDA Soil Taxonomy) and FAO systems. Conventional parametric and non-parametric land suitability evaluation systems as well as Geographic Information System (GIS) methods were used to generate suitability ratings for rubber cultivation. Dry rubber yield from existing plantations on the two sites obtained in the 2005/2006 and 2006/2007 cropping seasons were used to validate the suitability ratings. Effects of soil and weather parameters on rubber yield were determined. Influence of the three stages of development of rubber plantations on soil properties were compared with forest and arable land use types. Data were analysed using descriptive statistics, correlation, concordance, path analysis and ANOVA at p = 0.05. The soils studied were classified as Alagba, Orlu, Kulfo and Ahiara series at Iyanomo and Uyo, Calabar and Etinan Series at Akwete. The soils were in the Ultisol and Inceptisol soil orders of the Soil Taxonomy. The Ultisols covered 73.1 % and 70.9 % of the study area at Iyanomo and Akwete respectively; while Inceptisol covered 26.9 % and 29.1 % at Iyanomo and Akwete respectively. Soil maps produced by GIS and conventional method were not significantly different. Parametric and non-parametric land suitability evaluation rated 73.1 % and 26.9 % of studied area at Iyanomo as moderately suitable (S2) and marginally suitable (S3) respectively but 70.9 % and 29.1 % of Akwete site as S3 and not suitable (NS) respectively. The GIS method however rated 88.0 % of the Iyanomo site as highly suitable (S1) and 12.0 % as S2 and 52.8 % and 47.2 % of Akwete site as S1 and S2 respectively. Correlation between soil classes and actual rubber yield were not significant in 2005/2006 and 2006/2007 cropping seasons but soil classes significantly correlated with yield index in 2006/2007 season for both sites. Observed yield index ranged between 79.9 – 124.0 in 2005/2006 and 71.4 – 195.1 in 2006/2007 and were higher than the expected indices from conventional evaluation systems. Correlation coefficients of rainfall (r = 0.340*), humidity (r = - 0.245**), and path analyses revealed that relative humidity, K, bulk density and porosity were factors that significantly affect rubber yield. Majority of the soils were Ultisols and Inceptisols and were suitable for rubber production. Suitability evaluation with Geographic Information System is better than conventional methods in predicting yield of rubber.